PEMETAAN PREDIKSI SEBARAN KERENTANAN LONGSOR DI KECAMATAN TAWANGMANGU, KABUPATEN KARANGANYAR MENGGUNAKAN PENDEKATAN FUZZY LOGIC - Mualif Adi Saputra; Mochtar Lutfi Rayes; Istika Nita (Jurnal Tanah dan Sumberdaya Lahan, 2019)
Tawangmangu District is one of the problemas areas in Karanganyar Regency related to landslides. Land use that is not in accordance with the slope and triggered by high rainfall makes the District of Tawangmangu an area with criteria of landslides of medium to high criteria. Mitigation efforts need to be carried out to minimize the danger of landslides. Data limitations are the basis for these mitigation efforts. This can be solved using fuzzy logic. This method can be used by looking at a limited area and data. This research was conducted in Tawangmangu District by dividing the research location into 16 land map units (LMU). The results showed that Tawangmangu District was divided into four classes, involve: not vulnerable, low, medium and high. Criteria are not vulnerable to spread in 9; 7; 11; 10 and 12 LMU, low spread in 3; 4; 5; 16; 8 and 13 LMU, medium spread in 2; 15 and 1 LMU and high vulnerability only in 14 LMU. Factors that can take effect the occurrence of landslides in Tawangmangu District are slope, land use and bulk rainfall. This method can be applied at research sites because it has the accuracy of very accurate results.